HUBUNGAN HIGIEN PERSONAL DENGAN INFESTASI SOIL TRANSMITTED HELMINTHS PADA IBU HAMIL DI KELURAHAN SRI MERANTI DAERAH PESISIR SUNGAI SIAK PEKANBARU - Ratna Mega Sary; Lilly Haslinda; Yanti Ernalia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Intestinal worm infestation is still one of the public health problems reported in low-income and middle-income countries including Indonesia. Personal higiene and environment are important factors influencing the transmission of this desease. The objective of this research was to analyse the relationship between personal hygiene and Soil Transmitted Helminth (STH) infestation on pregnant women in the kelurahan Sri Meranti of coastal area Sungai Siak Pekanbaru. This analytic study using cross sectional approachment. Samples were taken by total sampling method, as many as 30 people. Bivariate analysis was conducted by using chi square test and Fisher test with the confidence interval of 95%. The result showed that of 8 of 30 respondents had infested STH (26,7%) with Ascaris lumbricoides and Trichuris trichiur. There conformation were collected, it the was relations between personal hygiene and STH, with collected information such as footwere used, toilet utilization, soap utilization habit right before meal and after defecation, cutting hails habit and wash vegetables before comsumption.Key work: personal Hygiene, soil transmitted helminthes infestation